Instability of Candida albicans hybrids. - Whelan, W L (1985)
Total cellular DNA content, determined by a colorimetric method, was used as an index of ploidy in Candida albicans. Mononucleate hybrids were formed by fusion of spheroplasts derived from diploid parent strains. Five hybrids, of six studied, were taken to be tetraploid on the basis of estimated DNA content. One hybrid was taken to be hexaploid or near-hexaploid. Selection for increased resistance to 5-fluorocytosine in the hybrids, which were heterozygous for resistance, resulted in isolation of variants which were of lower ploidy than the hybrids from which they originated. Variants were obtained which corresponded (in measured DNA content) to aneuploid, triploid, and diploid states. These results may form the basis of a cyclic parasexual system (2n X 2n----4n----2n) for genetic analysis of this asexual species.